The Effect of The Values of Peace on The Ability of Youth to Face VUCA Era (VUCA Prime) - Siti Hardianti Darma Pertiwi; Idayanti Nursyamsi; Abdul Razak Munir (SEIKO : Journal of Management & Business, 2023)
VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) is a phenomenon that can cause significant changes in an organization. However, the success of the organization in dealing with these changes is not only obtained by understanding VUCA but also by preparing itself for a strategy to deal with VUCA. The strategy is named VUCA Prime (Vision, Understanding, Clarity, Agility). This study connects the values of peace promoted by the KITA Bhinneka Tunggal Ika Foundation in the Peace Leadership Education program "Guardians of Peace" with VUCA Prime. This study aims to analyze the effect of the peace values by KITA Bhinneka Tunggal Ika on the youths’ ability to face the VUCA era. The research approach used is descriptive-quantitative by giving a questionnaire to sixty youths who participated as ‘Guardians of Peace’ KITA Academy which was followed by a regression analysis method. The result showed a positive and significant influence of the Value of Peace variables on VUCA Prime with The significance level value is 0.000, which is less than 0.05 and the t-count value is 4.633 which is greater than the t-table 2003. The direct effect given is 0.520 or 52%. With this result, we can deduce the value of peace is essential in preparing a leadership development plan to face the VUCA era. Keywords : Value of Peace, VUCA Prime, and VUCA